Experimental study on heat transfer enhancement using combined surface roughening and macro-structures in a confined double-nozzle spray cooling system - Liu, Pengfei (2022)
An experimental study is conducted to characterize the effects of surface roughness and the combined effects of surface roughening and macro-structure topology on the spray cooling heat transfer. It was found that the spray cooling thermal performances increase as the surface roughness increases. From the experimental results, a power law relationship is established between the heat flux and the magnitude of normalized roughness. On this basis, an empirical correlation is developed for spray cooling heat transfer on structured flat surfaces with varying roughness. The correlation is found to have an accuracy of 15%. In addition, the experimental results on the straight finned surfaces are compared with a region-based model with the surface roughness effect incorporated in the developed empirical correlation. The analysis reveals a decoupling relationship between the micro-roughness and macro-structure enhancing mechanisms. Furthermore, a decoupling analysis suggests that the micro-roughness enhancement and the macro-structure enhancement dominate the 0.5 mm pin finned surface and the 1.0 mm pin finned surface, respectively. However, the two types of enhancing mechanisms have a comparable contribution to spray cooling heat transfer enhancement on the straight finned surfaces. In general, spray cooling heat transfer can be enhanced by around 116% by increasing surface micro-roughness whereas heat transfer enhancement can reach as high as 136% and 288% on the surfaces with macro straight fin and pin fin structures containing micro-roughness, respectively.